Realisasi Supervisi Akademik dan Dampaknya terhadap Kinerja Guru dan Mutu Pendidikan di Madrasah: Kajian Literatur Sistematis - Isna Susmita; Mirna Rasuani; Fitri Aprilianty (Journal of Innovation in Teaching and Instructional Media, 2025)
This study aims to examine academic supervision and its impact on teacher performance and the quality of education in madrasah through a Systematic Literature Review approach based on the PRISMA guide. Academic supervision is a crucial component of educational management, especially in supporting teacher professionalism and educational quality. This review analyzes 15 scientific articles published in the last seven years, which discuss the implementation, techniques, and outcomes of academic supervision in madrasah settings. The findings reveal that academic supervision significantly contributes to improving pedagogical competence, discipline, responsibility, and the use of educational technology among teachers. However, the implementation of supervision also faces challenges such as inadequate supervisory skills among madrasah principals, lack of training, and weak organizational collaboration culture. This study provides a scientific mapping of academic supervision practices and offers recommendations to strengthen the capacity of madrasah principals in carrying out effective and sustainable supervision.